Cationic Trialkylphosphates: Synthesis and Transfection Efficacies Compared to Phosphoramidate Analogues. Issue 36 (31st October 2014) - Le Corre, Stéphanie S.; Berchel, Mathieu; Le Gall, Tony; Haelters, Jean‐Pierre; Lehn, Pierre; Montier, Tristan; Jaffrès, Paul‐Alain
Abstract: We report herein the synthesis of a novel family of cationic lipids, characterized by a trimethylammonium headgroup linked through a phosphate function to either two identical or two different lipid chains. The novelty of this study arises from the use of a trialkyl phosphate group to associate the hydrophobic domain to the cationic polar head. The structure of these new cationic lipids, which differs from that of previously reported lipophosphoramidates, is closer to the phospholipids encountered in the plasma membrane, and possesses a phosphocholine polar head. Evaluation of the transfection activity allowed us to compare the efficacy of cationic lipophosphates with that of lipophosphoramidates. These results demonstrate that cationic lipophosphates and lipophosphoramidates having otherwise identical chemical structures exhibit similar transfection efficacies. The second conclusion is that the structure of the lipid domain is a much more important parameter in governing transfection efficacy than the composition of the linker moiety. The best results were obtained with cationic lipophosphates or lipophosphoramidates possessing two different lipid chains, for example one oleyl chain with one phytanyl chain. These nonsymmetric cationic lipids exhibited transfection efficacies that were 10‐ to 200‐fold better than those obtained with Lipofectamine used as a commercial standard. Abstract : Cationic symmetric and nonsymmetric trialkylphosphates were synthesised. These vectors were evaluated for gene delivery in four human‐derived cell lines and compared to their equivalent lipophosphoramidates.